Relationships between mental toughness and psychological wellbeing in undergraduate students. (March 2015) - Stamp, Elizabeth; Crust, Lee; Swann, Christian; Perry, John; Clough, Peter; Marchant, David
Highlights: Mental toughness found to be a moderate/strong predictor of psychological wellbeing. Age, gender, and year of study did not predict wellbeing. Mental toughness appears important to student wellbeing in higher education. Abstract: This study examined relationships between mental toughness (MT) and psychological wellbeing (PWB) in undergraduate students. Following previous research that identified significant and positive relations between MT and academic performance, it was hypothesised that MT would predict PWB within a student population. Participants were undergraduate students ( n =  168) from nine United Kingdom universities. The sample included participants from a range of different degree programmes and from all three years of standard undergraduate study. Online questionnaires were completed to assess MT and PWB. Multiple linear regression analyses found that components of MT were moderate to strong predictors of PWB with between 35% and 64% of variance explained. Importantly, age, gender, and level of study were not found to predict PWB. These findings are consistent with stated hypotheses and further demonstrate the potential importance of MT within educational settings.